Awareness of and adherence to the food based dietary guidelines among household meal planners in the Philippines - Lopez-Madrid, Marilou M.; Acuin, Cecilia Cristina S.; Orense, Consuelo L.; Duante, Charmaine A.; Tan, Robby Carlo A.; Capanzana, Mario V. (2018)
The study was conducted to determine the awareness of and adherence to the food-based dietary guidelines (FBDGs) among household meal planners in the Philippines. The data were collected from 9754 meal planners nationwide during the conduct of the 2015 Updating Survey of Nutritional Status of Filipino Children and Other Population Groups. A pre-tested survey questionnaire was administered to the respondents by trained researchers through face-to-face interview. Questions included were on awareness about the four FBDGs ? 2012 Nutritional Guidelines for Filipinos (NGF); Kumainments (localized and simplified version of NGF); Pinggang Pinoy® (a plate-like pictorial model); and the Daily Nutritional Guide Pyramid (DNGP) ? and food intake practices relative to the 2012 NGF. Findings of the study showed low nationwide reach of the four FBDGs. The meal planners were most aware of the DNGP (35.8%) and Kumainments (27.5%). They have least awareness on Pinggang Pinoy® (10.6%). The most often recalled message was ?Eat fruits and vegetables? in the NGF (28.1%) and in Kumainments (35.2%), while about 25% mentioned ?Eat a variety of foods everyday?. The respondents had limited adherence to the dietary guidelines. The most adhered message was ?limit intake of salty, fried, or fatty and sugar-rich foods? (74?91%), while only one-half of the respondents adhered to the guideline ?eat a variety of foods everyday?. Intake of other food/food groups (vegetables, protein-rich foods, and calcium-rich foods) was done about 2?4 times per week. There is a need to strengthen and harmonize the dissemination efforts of FBDGs not only among meal planners, but also among various segments of the population using various media channels. Continued refinement of communication strategies used for FBDG implementation ? as well as regular monitoring and evaluation ? should be done to improve FBDG?s usefulness and effectiveness.